A SUMMARY OF THE NATIONAL CARE OF THE DYING AUDIT FOR HOSPITALS, ENGLAND (NCDAH) 2013/14 AUDIT RESULTS. Issue 1 (1st March 2015) - Mulholland, Helen; Gambles, Maureen; Lowe, Derek; Husk, Janet; Stewart, Kevin; Ellershaw, John
Abstract : Introduction: The quality of end of life services is suggested as an indicator of the quality of all health care provision. NCDAH provides data regarding the standard of care delivered to imminently dying patients. Aim(s) and method(s): To report on the care provided to dying patients and their relatives to highlight areas for improvement in clinical practice and influence policy/funding/research agendas. Retrospective audit of organisational aspects of care & clinical data from 6580 patient records for May 2013 from 131 Hospitals (H). 36H (27%) captured 858/2313 (37% response) bereaved relatives' (BR) views via the Care of the Dying Evaluation questionnaire. Results: Median age 82; cancer diagnosis 23% (1546); female 51% (3332). Organisational 7-day-access to specialist palliative care service (SPCS) in 28H (21%). No education/training provision in 24H (18%). No Trust Board (TB) representation in 61H (47%). No Audit in 57H (44%). Clinical Decisions and assessments routinely recorded (eg.Recognition of dying recorded in 87% (5722) cases). Exceptions-Clinically Assisted Nutrition 45% (2563)/Hydration 59% (3351). Communication of decisions more likely undertaken with relatives than patients. Least routinely recorded: Spiritual needs assessment(Capable patients 21% (715/3391)*/Relatives 25% (1623/6575*)). Care after death 46% (3037) BR Views Most reported that patients were 'always' treated with dignity & respect by doctors (66%/535*) and nurses (70%/577*) BR felt adequately supported (76%/610*) *Reduced sample Conclusion(s): Organisational processes should include: 7 day access to SPCS; staff education; Trust Board representation/audit. Clinical decision documentation & communication to patients & relatives could be improved. Whilst bereaved relatives views were generally positive, a significant minority reported negative perceptions of care.